The intra-European transferability of graduates’ skills gained in the U.K. - Tzanakou, Charikleia; Behle, Heike (Journal of Ethnic & Migration Studies, 2017)
Mobility has been seen as the hallmark of the European Higher Education Area with student and graduate mobility being promoted and facilitated through the Bologna process. This paper follows the experiences of 12 U.K.-educated mobile graduates of British and other European Union (EU) nationality and analyses both their skills gained by studying at a U.K. higher education institution and the obstacles they experienced to transfer their U.K. qualification to a different country. We demonstrate that graduates not only developed – as part of their course and within the opportunities that the U.K. higher education environment offers – but also used various skills ranging from subject-specific to language and generic skills in their current activities. While a U.K. degree is reputable and well known in other European countries, there seem to be limitations in relation to its transferability and recognition for studying and working beyond the U.K., which contribute to unequal treatment in the local labour market between domestic- and foreign-educated graduates. More than a decade after the inception of the Bologna process and the introduction of tools to facilitate mobility, structural barriers still exist which prevent the smooth recognition of skills and qualifications of mobile students and graduates within the EU. This has implications for further study and employment outcomes for mobile graduates but also for mobility decisions before and after higher education.